2016
DOI: 10.1155/2016/4896487
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Elevation of Alkaline Phosphatase in a Pregnancy Complicated by Gestational Diabetes and Infant with Neonatal Alloimmune Thrombocytopenia

Abstract: There have been few case reports of isolated elevation of alkaline phosphatase beyond the normal physiologic amount with subsequent return to baseline after delivery. Here we present a similar case of extreme elevation of alkaline phosphatase in a pregnancy complicated by gestational diabetes and subsequently by neonatal alloimmune thrombocytopenia (NAIT).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…A case control study by Rajagambeeram et al further supported this finding and showed that total serum ALP and placental (heat stable) ALP were significantly elevated in women with hypertensive disorders of pregnancy versus controls [ 11 ]. Other cases reported associations with preterm delivery [ 8 , 14 ], preterm premature rupture of membranes [ 15 ], gestational diabetes [ 14 , 16 , 17 ], and intrauterine growth restriction [ 8 ]. One case report interestingly noted thrombocytopenia in the mother with extremely elevated placental isoenzymes, and upon further investigation was found to have several relatives with elevated baseline ALP suggesting a possible genetic link [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…A case control study by Rajagambeeram et al further supported this finding and showed that total serum ALP and placental (heat stable) ALP were significantly elevated in women with hypertensive disorders of pregnancy versus controls [ 11 ]. Other cases reported associations with preterm delivery [ 8 , 14 ], preterm premature rupture of membranes [ 15 ], gestational diabetes [ 14 , 16 , 17 ], and intrauterine growth restriction [ 8 ]. One case report interestingly noted thrombocytopenia in the mother with extremely elevated placental isoenzymes, and upon further investigation was found to have several relatives with elevated baseline ALP suggesting a possible genetic link [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…As stated earlier, previous studies tried to understand the mechanism behind this abnormal elevation, which is not fully understood. It was suggested a correlation between ALP elevation and several perinatal complications such as preterm delivery [ 3 ], gestational diabetes [ 5 ], large for gestational age fetuses [ 6 ], and intrauterine growth restriction [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there are currently few reports describing abnormally high serum ALP in pregnancy, some studies have shown that this enzyme could be an obstetric and perinatal marker associated with preterm delivery [3], hypertensive disorders [4], gestational diabetes [5], large for gestational age fetuses [6], and intrauterine growth restriction [7]. The exact mechanism of this association remains unknown, but it is hypothesized it may be the result of placental insufficiency [3].…”
Section: Introductionmentioning
confidence: 99%
“…It is almost three decades since the publication of Brock,9 Best10 and Meyer’s4 work on maternal serum ALP and its association with placental-mediated fetal problems. Little has appeared in the interim apart from sporadic and isolated case reports 6–8 11…”
Section: Discussionmentioning
confidence: 99%